O pensamento fenomenológico na formação do psicólogo: uma experiência de ensino na graduação - Gomes, Luciana Szymanski Ribeiro (2006)
How does the process of teaching and learning the phenomenological thought unfold in the graduation studies of Psychology? This question is the backbone of the present work: in order to answer it I started from the very experience of elaboration and practice of teaching the disciplines connected to Phenomenology in a graduation course in São Paulo, Brazil. The phenomenological thought was present along the whole course as a proposal of granting equivalent time for the discipline as that given in the curriculum for other approaches to Psychology. Starting with the description of my own path in Psychology and the place Phenomenology took in it this work I am first of all motivated by the question: what is it, the teaching of Phenomenology?. This work proposes a more detailed description of the process of teaching Phenomenology in which I have been participating, what allowed me the analysis of inserting some phenomenological notions in Psychology, its developments in practical clinical situations, in research and in educational fields. I have underlined the movement of being back to the things themselves fundamental thinking in the Phenomenology of Edmund Husserl, relating it to the phenomenological attitude here understood as a possibility of thinking the phenomenon in Psychology studies or further, as a way of being in the world. Therefore, this work contains a dialog between the course in its concept before the classes and the course that had actually been realized in classroom. Following it another question came up: What is it, the learning of Phenomenology? I focused the debate on the student s perception in order to go deep in their experiences and their points of view (difficulties and insights) on the process of appropriation of the phenomenological thought. Their experiences complement mine, as the process of teaching and learning here is understood from the unity teacher-student: for learning and teaching is not an independent situation but a correlating one. Their perceptions emphasize the importance of looking at the studied phenomenon as it is disclosed and not from theoretical and judgmental a priori, considering the methodological suspension (epoché) The students called attention to the perception of a comprehensive attitude instead of a theoretical one (explanations), hegemonic in the academy today. Finally, after describing the experiences of teaching and learning the disciplines linked to Phenomenology and tuned with the perceptions of these students, I suggest some possible contributions that Phenomenology may have in the Psychology professional practice of. In order to describe these contributions I have considered a coordinate line revealed in the phenomenological thought that crosses different tendencies, works and authors: the phenomenological attitude . Thus, not ignoring the existence of various phenomenological studies which sometimes do not agree among themselves, I focus some common aspects that are important in the context of Psychology graduation studies. They are: critic related to the distance to be taken from the world in order to understand it and critic towards the necessity of explaining the world from pre-defined theoretical concepts. These are characteristics of the dichotomy thinking inherited from the Positivism of the 19th century still present in contemporary Psychology. This critical approach of the phenomenological thought may bring some contributions to the Psychology studies as it exposes notions as for example, intentionality, as well as other notion when it proposes a breakthrough in the dichotomy subject-object inaugurating another way of looking at the so called reality . Reality in the phenomenological perspective is always understood from a specific point of view or experience: the truth therefore, is rather a possible perception than a theoretical or technical a priori, commonly dictated by someone possessing academic or scientific knowledge